A carbon quantum dot and a method for quantitatively detecting tumor vascular inhibitor DX1002

By using carbon quantum dots prepared from specific raw materials as fluorescent probes, the quantitative analysis problem of DX1002 in biological samples was solved, and the rapid, sensitive, economical and high-throughput detection effect was achieved, simplifying the sample pre-processing process.

CN115684099BActive Publication Date: 2025-03-28DONGGUAN ANHAO PHARMA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110846785.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-26
Publication Date
2025-03-28
Estimated Expiration
2041-07-26

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high resolution, high sensitivity, rapid, economical and high throughput quantitative analysis of the tumor vascular inhibitor DX1002, especially in the detection in biological samples, where there are problems of cumbersome sample preprocessing and large errors.

Method used

Carbon quantum dots prepared from orthophenylenediamine, tryptophan and iron salts were used as fluorescence probes to construct quantitative detection methods by undergoing specific fluorescence intensity changes with DX1002, simplifying the sample pre-processing process and achieving high-throughput analysis.

Benefits of technology

Fast, sensitive, economical and high-throughput quantitative detection of DX1002 is achieved, reducing analysis time and error, and is suitable for pharmacokinetic monitoring and tissue distribution research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115684099B_ABST
    Figure CN115684099B_ABST
Patent Text Reader

Abstract

The present invention provides a carbon quantum dot, which is prepared from the following raw materials: o-phenylenediamine, tryptophan, and iron salt. The carbon dot of the present invention has stable fluorescence, excellent optical properties such as resistance to biological background quenching, and the characteristic of being specifically quantitatively quenched by DX1002. The carbon dot is used as a fluorescent probe to construct a method for quantitatively detecting DX1002. The method can skip tedious sample pretreatment and separation of interferences, is a rapid, sensitive, economical, and high-throughput DX1002 analysis method, is suitable for in vivo pharmacokinetics monitoring of DX1002, promotes further analysis and research on anticancer candidate drug DX1002, and also provides new methods and ideas for the high-throughput detection application of carbon quantum dots in biological samples, so as to better meet the rapid detection needs of hospitals and testing centers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fluorescent probe detection, and specifically relates to a carbon quantum dot and a method for quantitatively detecting a tumor blood vessel inhibitor DX1002. Background Art

[0002] In recent years, the incidence and mortality of tumors around the world have continued to rise. In China, the incidence and mortality of lung cancer have ranked first in the world. Due to the situation, the continuous research and development and progress of anti-tumor drugs are imminent. Moreover, the research and development focus of anti-tumor drugs has shifted from traditional cytotoxic drugs to multi-link target drugs, such as new blood vessels, cell signal transduction molecules, improving immunity, reducing the shedding of cancer cells, etc. DX1002 is a butylammonium salt of phenylacrylic acid independently developed in my country, with the following structure:

[0003]

[0004] DX1002 is slightly soluble in water, with a pKa of 6.8 and a maximum absorption wavelength of 314nm. It is an organic weak acid ammonium salt. The synthesis route of DX1002 was completed in 2006, and a national patent (ZL 200610020818.5) was applied for. In November 2017, it was approved by the State Food and Drug Administration (CFDA) for clinical trials to enter Phase I clinical trials. It is a candidate drug for Class 1.1 tumor vascular inhibitors, mainly used for solid cancers such as thyroid cancer, lung cancer, and digestive tract cancer. According to the requirements of CFDA, the pharmacokinetic / pharmacodynamic (PK / PD) relationship of DX1002 needs to be studied in depth during clinical trials.

[0005] However, the study of in vivo pharmacokinetics has always required high-resolution, high-sensitivity analytical techniques, such as LC-MS / MS, and a large number of analytical samples. In order to reduce the matrix effect, tedious sample pretreatment must be completed to purify the sample to be tested. The process is not only time-consuming and labor-intensive, but may also introduce a lot of errors, causing deviations in the analysis results. Spectroscopy is generally considered to have high-throughput detection capabilities, but its biggest drawback is poor specificity. Especially for biological samples with complex endogenous impurities, spectroscopy cannot be used directly for detection. How to establish a specific, highly sensitive, high-throughput and high-precision analysis method has become one of the unremitting goals of analysts in the field of drug analysis. Although today's UHPLC-MS technology has greatly shortened the detection time, the tedious pretreatment process continues to limit the total analysis time and error.

[0006] Carbon quantum dots, also known as carbon dots for short, are a new type of zero-dimensional carbon nanomaterial (diameter ≤ 10nm) following nanomaterials such as fullerenes, carbon nanotubes and graphene. They can usually be divided into graphene quantum dots (GQDs), carbon nanodots (CNDs) and polymer dots (PDs). They were discovered by chance in 2004 by the Xu team at the University of South Carolina in the United States. When they used electrophoresis to purify arc discharge ash to prepare single-walled carbon nanotubes, they unexpectedly observed carbon nanoparticles that could emit fluorescence. Until 2006, the Sun team of scientists at Clemson University in the United States used laser ablation of carbon targets (obtained by hot pressing of graphite powder and adhesive) and organic reagent surface passivation treatment to prepare carbon nanoparticles with a particle size of less than 10nm that can emit strong fluorescence in solution and solid state. They formally named this fluorescent carbon nanoparticle carbon dots (CDs). Compared with organic fluorescent dyes, the excitation and emission spectra of carbon dots are wide and continuous, showing the characteristics of single excitation and multi-emission; high-stability fluorescence, resistant to photobleaching, can achieve long-term labeling in living tissues; and the emission wavelength is adjustable. Compared with traditional semiconductor quantum dots, carbon dots have good biocompatibility and lower toxicity, and do not contain heavy metal elements. These advantages of carbon dots have gradually attracted people's attention and become a hot topic of current research. It has shown great application potential in the fields of living imaging, biochemical sensing, analytical detection, etc.

[0007] If DX1002 can be used as the target drug and carbon dots that undergo specific fluorescence intensity changes with DX1002 can be prepared, and the quantitative relationship between the change in carbon dot fluorescence intensity and the DX1002 concentration can be used to first construct an in vitro carbon dot fluorescent probe for DX1002 content determination fluorescence analysis, it will greatly facilitate the development of a faster, more sensitive, and less expensive DX1002 quantitative analysis method for PK research on DX1002.

[0008] However, although the preparation process of CDs has made great progress, its low yield and low quantum yield have always been the current bottleneck. First, the preparation process of CDs is greatly affected by external conditions. Even if the carbon source used is the same and the preparation process is the same, the fluctuation of reaction conditions (reaction temperature or reaction time) will directly affect the surface structure of the prepared CDs, resulting in differences in the physical and chemical properties of CDs, especially differences in fluorescence characteristics. Secondly, studies have shown that surface passivation and heteroatom doping will improve the fluorescence quantum yield of carbon dots and change the surface structure to provide active sites. When the selected dopants are different, the different addition amounts will also affect the surface structure of carbon dots. Therefore, it is very difficult to prepare CDs that have a specific effect on DX1002 and have a quantitative relationship with DX1002. In addition, the CDs also need to avoid the interference of biological media in biological samples such as plasma samples and tissue samples on the fluorescence bleaching of carbon dots. Therefore, in order to achieve quantitative detection of DX1002, high requirements are placed on the various properties of carbon dots. Summary of the invention

[0009] The purpose of the present invention is to provide a carbon quantum dot that has a specific effect on DX1002 and a quantitative relationship with DX1002, and a high-throughput DX1002 mouse pharmacokinetics study and tissue distribution analysis method that can skip tedious biological sample pretreatment and separation.

[0010] The invention provides a carbon quantum dot, which is prepared from the following raw materials: o-phenylenediamine, tryptophan and iron salt.

[0011] Furthermore, the iron salt is at least one of ferric chloride or its hydrate, ferric sulfate or its hydrate.

[0012] Furthermore, the above iron salt is ferric chloride hexahydrate.

[0013] Furthermore, the molar ratio of the above-mentioned o-phenylenediamine, tryptophan and iron salt is: 4:1:(1.2-12), preferably 4:1:7.

[0014] The present invention also provides a method for preparing the above-mentioned carbon quantum dots, comprising the following steps:

[0015] (1) taking o-phenylenediamine, tryptophan and iron salt in proportion and dissolving them in an aqueous solution of hydrochloric acid;

[0016] (2) react at 180-220°C for 1-5 hours, cool and filter to obtain the filtrate, and dry to remove the solvent to obtain;

[0017] Preferably, the reaction in step (2) is carried out at 200° C. for 3 h.

[0018] The present invention also provides the use of the carbon quantum dots in a reagent for quantitatively detecting the tumor vascular inhibitor DX1002.

[0019] The present invention also provides a reagent for quantitatively detecting the tumor blood vessel inhibitor DX1002, which contains the above-mentioned carbon quantum dots.

[0020] The present invention also provides a method for quantitatively detecting the tumor vascular inhibitor DX1002, comprising the following steps:

[0021] (1) taking the above-mentioned carbon quantum dots, dissolving them in pure water to obtain a carbon quantum dot solution, and measuring the fluorescence intensity F0 of the carbon quantum dot solution;

[0022] (2) adding the carbon quantum dot solution of step (1) to the sample to be tested and mixing to obtain a solution to be tested; and measuring the fluorescence intensity F of the solution to be tested;

[0023] (3) Substituting the fluorescence intensities F and F0 measured in steps (1) and (2) into the regression equation F0 / F=f(Q), the Q value is calculated to be the concentration of DX1002;

[0024] Wherein, the sample to be tested is plasma, and the regression equation is: F0 / F=0.0024Q+1.0053;

[0025] Or, the sample to be tested is liver tissue fluid, and the regression equation is: F0 / F=0.0021Q+0.9981;

[0026] Or, the sample to be tested is lung tissue fluid, and the regression equation is: F0 / F=0.0021Q+0.9986;

[0027] Or, the sample to be tested is renal tissue fluid, and the regression equation is: F0 / F=0.0021Q+1.0186;

[0028] Preferably, the measurement conditions of steps (1) and (2) are to measure the fluorescence intensity at an emission wavelength of 610 nm under an excitation wavelength of 560 nm.

[0029] Furthermore, the concentration of DX1002 in the above-mentioned test sample is 7.5-250 μg / mL.

[0030] Furthermore, the concentration of carbon quantum dots in the test solution in the above step (2) is 0.125-2.5 mg / mL, preferably 0.25 mg / mL.

[0031] The regression equation F0 / F=f(Q) indicates that there is a mathematical functional relationship between Q and F0 / F; in the field of mathematics, function f(x) indicates the equivalent relationship between elements in a number set and elements in another number set: given a number set A, assuming that the element is x, applying the corresponding rule f to the element x in A, denoted as f(x), another number set B is obtained, assuming that the element in B is y, then the equivalent relationship between y and x can be expressed by y=f(x). Therefore, the regression equation F0 / F=f(Q) of the present invention indicates an equivalent relationship between Q and F0 / F, and f is the corresponding rule.

[0032] The carbon dots of the present invention have excellent optical properties such as stable fluorescence, anti-biological background quenching ability, and can be quantitatively quenched by DX1002. Using them as fluorescent probes, a CDs-DX1002 fluorescence quenching quantitative method was constructed in vitro, and the method was used for the pharmacokinetics and tissue distribution analysis of DX1002 for the first time. The DX1002 quantitative detection method of the present invention can skip the cumbersome sample pretreatment, and is a fast, sensitive, economical, and high-throughput DX1002 analysis method suitable for the pharmacokinetic monitoring of DX1002. By using the 96-well plate determination of the microplate reader, the unit sample analysis time is only 0.25min, which is 22 times faster than the HPLC-MS / MS detection method (t analysis 10min), and for the first time, ultra-high-speed determination of biological samples in a true sense is realized, so as to promote further analysis and research of a class of innovative anticancer candidate drugs DX1002. It also provides new methods and ideas for the high-throughput detection application of carbon quantum dots in biological samples, and better realizes the rapid detection needs of hospitals and testing centers.

[0033] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0034] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 : The relationship between F0 / F of the OT-FeCDs detection system and different DX1002 concentrations; the embedded figure is the linear relationship between F0 / F of the OT-FeCDs detection system and DX1002 in the concentration range of 7.5 to 250μ.

[0036] Figure 2 : (A) TEM image of OT-FeCDs; (B) FT-IR spectrum of OT-FeCDs.

[0037] Figure 3 Figure 3: Stability study of the effects of salt ion concentration (A), pH (B), UV irradiation time (C), and room temperature storage time (D) on the fluorescence intensity of carbon dots.

[0038] Figure 4 Figure 3 is the relationship between the concentrations of different OT-FeCDs in the detection system and the fluorescence quenching of DX1002.

[0039] Figure 5 Figure 3: The relationship between F0 / F and different DX1002 concentrations of SOCDs, OCDs, OTCDs, and OFCDs carbon dot detection systems.

[0040] Figure 6 Figure 2: The quenching relationship between carbon dots OT-FeCDs and DX1002 at different temperatures.

[0041] Figure 7 Figure 2: Fluorescence spectrum of OT-FeCDs after mixing with biological tissue.

[0042] Figure 8 This is the drug-time curve of DX1002.

[0043] Fig. 9 For: Tissue distribution of DX1002. DETAILED DESCRIPTION

[0044] The o-phenylenediamine of the present invention was purchased from Tianjin Komeo Chemical Reagent Co., Ltd.; tryptophan was purchased from Shanghai McLean Biochemical Technology Co., Ltd.; rhodamine 6G and quinine sulfate (98%) were purchased from Shanghai McLean Biochemical Technology Co., Ltd.; CaCl2, KCl, and MgCl2 were purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd.; NaCl, CuCl2, and concentrated hydrochloric acid were purchased from Guangdong Chemical Reagent Engineering Technology Research and Development Center; FeCl3·6H2O was purchased from Chengdu Kelong Chemical Reagent Factory; sucrose and glucose were purchased from Tianjin Komeo Chemical Reagent Co., Ltd.; leucine, glycine, histidine, and alanine were all purchased from Shanghai McLean Biochemical Technology Co., Ltd.; all reagents used in the experiment were analytical grade. DX1002 was made by Guangzhou Anhao Pharmaceutical Technology Co., Ltd.

[0045] Experimental animals: Kunming mice (5-6 weeks old, female, weight 18-24 g, purchased from Chengdu Dashuo Experimental Animal Co., Ltd.)

[0046] Example 1. Synthesis of Carbon Quantum Dots of the Present Invention

[0047] Weigh 0.108g of o-phenylenediamine, 0.05g of tryptophan, and 0.5g of FeCl3·6H2O, add 200μL of concentrated hydrochloric acid, add 10ml of water, dissolve by ultrasonication, mix evenly, place in a reaction kettle, heat at 200℃ for 3h, cool and transfer out, filter to obtain the carbon quantum dots (OT-FeCDs) solution of the present invention, and freeze-dry to obtain a black powdery solid, which is the carbon quantum dots OT-FeCDs of the present invention.

[0048] Example 2: Establishment of the method for quantitative detection of DX1002 by carbon quantum dots of the present invention

[0049] Take 250 mg of DX1002 reference substance, weigh accurately, add 100 mL of ultrapure water, dissolve by ultrasonication, transfer to a 250 mL brown volumetric flask, and dilute to scale with ultrapure water to obtain a 1 mg / mL DX1002 reference substance solution. Dilute this solution to a series of concentrations for later use.

[0050] Determination method: accurately measure 50 μL of the prepared OT-FeCDs solution (1 mg / mL) and DX1002 reference solution of different concentrations into a 0.5 mL EP tube, accurately add 100 μL of ultrapure water, and the OT-FeCDs concentration in the test solution after mixing is 0.25 mg / mL. Accurately measure 170 μL of the mixed solution system into a 96-well plate, and use an enzyme reader to measure the fluorescence value of each well (Ex / Em=560 / 610 nm) to obtain the fluorescence intensity F of DX1002 solutions of different concentrations after the action of OT-FeCDs, and make a fluorescence quenching degree (F0 / F)-concentration (Q) standard curve (F0 is the fluorescence intensity of the system without the addition of quencher OT-FeCDs).

[0051] It was confirmed that OT-FeCDs and DX1002 had a good linear relationship in vitro. Figure 1 As shown, the two have a good linear relationship in the DX1002 concentration range of 7.5 to 250 μg / mL.

[0052] Based on the in vitro linear relationship, the linear relationship between the fluorescence intensity of the biological sample system and the concentration of DX1002 was investigated. The ultrapure water in the above determination method was replaced with the biological sample system: plasma, liver tissue homogenate, lung tissue homogenate, and kidney tissue homogenate, and the standard curve was prepared using the same method.

[0053] The results confirmed that within the DX1002 concentration range of 7.5 to 250 μg / ml, there was a good linear relationship between the fluorescence intensity of biological samples and the DX1002 concentration. The linear equation is shown in Table 1:

[0054] Table 1 Linearity and range of biological samples

[0055]

[0056] Therefore, the method for quantitative detection of DX1002 using carbon quantum dots OT-FeCDs is as follows:

[0057] (1) Take the carbon quantum dots OT-FeCDs of the claim and dissolve them in pure water to obtain a 1 mg / mL OT-FeCDs solution;

[0058] (2) adding the carbon quantum dot solution of step (1) to the sample to be tested (plasma, liver tissue homogenate, lung tissue homogenate or kidney tissue homogenate) and mixing to obtain a solution;

[0059] (3) Determine the fluorescence value (Ex / Em=560 / 610 nm) by using an enzyme marker: determine the fluorescence intensity F0 of the sample to be tested and the fluorescence intensity F of the solution in step (2);

[0060] (4) Substituting the fluorescence intensity F and F0 measured in step (3) into the regression equation F0 / F=f(Q), the Q value is calculated to be the concentration of DX1002;

[0061] Wherein, the sample to be tested is plasma, and the regression equation is: F0 / F=0.0024Q+1.0053;

[0062] Or, the sample to be tested is liver tissue fluid, and the regression equation is: F0 / F=0.0021Q+0.9981;

[0063] Or, the sample to be tested is lung tissue fluid, and the regression equation is: F0 / F=0.0021Q+0.9986;

[0064] Or, the sample to be tested is renal tissue fluid, and the regression equation is: F0 / F=0.0021Q+1.0186.

[0065] Comparative Example 1: Preparation of Carbon Quantum Dot SOCDs

[0066] Cut fresh spinach into small pieces, take an appropriate amount of spinach pieces and soak them in 80% ethanol solution for 30 minutes, filter the spinach extract, evaporate the filtrate (50°C) to remove ethanol, freeze-dry the resulting green clear solution, and collect the freeze-dried green powder, which is the carbon dot precursor. Take three portions of carbon dot precursor, 0.05g each, add 25mL ethanol to dissolve it to form a transparent solution. The above three solutions are transferred to a 50mL polytetrafluoroethylene reactor, heated at 120°C, 150°C, and 180°C for 6h, cooled naturally to room temperature, filtered with qualitative filter paper and 0.22μm filter membrane, and the filtrate is freeze-dried to obtain SOCDs loose powder.

[0067] The fluorescence properties of three SOCDs carbon dots obtained by reactions at different temperatures were investigated. Although there are certain differences, the same point is that they have dual emission. When the excitation wavelength increases from 380nm to 460nm, the emission in the blue-yellow region is excitation-dependent, while the emission in the near-infrared region is independent of the excitation wavelength. The maximum emission wavelength of the carbon dots is 680nm.

[0068] Comparative Example 2: Preparation of Carbon Quantum Dots OCDs

[0069] Weigh 0.2 g of o-phenylenediamine, add 10 mL of ultrapure water and 10 mL of ethanol, and after ultrasonic treatment for 10 min, transfer the above solution to a 50 mL polytetrafluoroethylene reactor and react at 180 ° C for 12 h. Filter with qualitative filter paper and 0.22 μm filter membrane respectively and freeze-dry to obtain OCDs powder.

[0070] When the excitation wavelength increases from 360nm to 460nm, the fluorescence intensity of OCDs first increases and then decreases. Its emission peak does not change with the excitation wavelength, and a maximum emission of 565nm can be generated under excitation at a wavelength of 420nm.

[0071] Comparative Example 3: Preparation of Carbon Quantum Dot OTCDs

[0072] Weigh 0.2 g of o-phenylenediamine and 0.335 g of tyrosine (the molar ratio of the two is 1:1) respectively and put them into a 50 mL beaker, add 10 mL of ultrapure water and 10 mL of ethanol in turn, and ultrasonically treat for 10 min. Transfer the above solution to a 50 mL polytetrafluoroethylene reactor and react at 180 ° C for 12 h. The product is filtered with qualitative filter paper and 0.22 μm filter membrane respectively and then freeze-dried to obtain OTCDs powder.

[0073] When the excitation wavelength increases from 360nm to 460nm, the fluorescence intensity of OTCDs first increases and then decreases, and its emission wavelength does not change with the change of excitation wavelength. Under the excitation of 380nm, it can produce the maximum emission of 565nm.

[0074] Comparative Example 4: Preparation of Carbon Quantum Dots OFCDs

[0075] Weigh 0.1 g of o-phenylenediamine and dissolve it in 10 mL of ethanol. Add folic acid aqueous solution (10 mg FA is added to 10 mL of pure water). After ultrasonic treatment for 10 min, transfer it to a 50 mL polytetrafluoroethylene reactor and heat it at 180°C for 12 h. Take out the reactant, filter it, and dry it to obtain OFCDs.

[0076] In the process of increasing the excitation wavelength from 360nm to 460nm, the fluorescence intensity of OFCDs-2 first increased and then weakened. The emission wavelength of the carbon dots was independent of the excitation wavelength and could produce a maximum emission of 572nm under excitation at a wavelength of 420nm.

[0077] The beneficial effects of the present invention are demonstrated by experimental examples below.

[0078] Experimental Example 1: Screening of the Raw Material Ratios of Carbon Quantum Dots of the Present Invention

[0079] According to the raw material ratio shown in Table 2, a series of OT-FeCDs carbon quantum dots were prepared with reference to the preparation method of Example 1, and their quantum yields were detected. The results are shown in Table 2.

[0080] Table 2 Screening of raw material ratios of OT-FeCDs carbon quantum dots

[0081]

[0082] It can be seen that when the molar ratio of o-phenylenediamine, tryptophan and iron salt is 4:1:7, the quantum yield of carbon quantum dots is the highest, and it is most suitable as carbon dots for detection.

[0083] Experimental Example 2: Characterization of Carbon Quantum Dots of the Present Invention

[0084] 1. Synthesis results of carbon quantum dots: A drop of OT-FeCDs solution prepared in Example 1 was dropped on a copper mesh and dried naturally. The morphology and particle size ( Figure 2 A), it can be seen that it is monodisperse spherical particles with uniform particle size concentrated at 5nm. Take freeze-dried OT-FeCDs powder and potassium bromide powder, mix them evenly in a certain proportion, and press them into transparent sheets. The infrared absorption spectrum is measured by infrared spectrometer ( Figure 2 B), it can be seen that at 3301.58cm -1 There is a broad absorption band, which is derived from the stretching vibration of OH and NH, 1055.83cm -1 The absorption at 1573.62cm–1 and 1481.30cm is attributed to CN stretching vibration. -1 The absorption at 40° can be attributed to the bending vibration of NH and CO. This indicates that the main elements of OT-FeCDs are C, N, and O and there are many hydroxyl groups and amino groups on the surface, which confirms the successful synthesis of OT-FeCDs carbon dots of the present invention.

[0085] 2. Conduct OT-FeCDs fluorescence stability test:

[0086] (1) Evaluation of the effect of ionic strength: NaCl solutions of different concentrations (0-12 mM) were added to a certain concentration of OT-FeCDs solution, and fluorescence measurements were performed in a fluorescence spectrophotometer equipped with a xenon lamp (RF-6000, Shimadzu, Japan). The concentration of the carbon dots solution in the measured solution system was 0.25 mg / mL. The results are shown in Figure 2. Figure 3 As shown in A, it shows that the ionic strength has no obvious effect on the fluorescence of OT-FeCDs.

[0087] (2) Evaluation of the effect of pH: A series of BR buffer solutions (pH = 2.0-11.0, 10% v / v) were added to a certain concentration of OT-FeCDs solution, and fluorescence measurements were performed in a fluorescence spectrophotometer equipped with a xenon lamp (RF-6000, Shimadzu, Japan). The concentration of the carbon dot solution in the measured solution system was 0.25 mg / mL. The results are shown in Figure 2. Figure 3 As shown in B, it shows that pH has no obvious effect on the fluorescence of OT-FeCDs.

[0088] (3) Evaluation of the effect of UV irradiation: The OT-FeCDs solution was continuously irradiated with UV for a certain period of time, and fluorescence was measured in a fluorescence spectrophotometer equipped with xenon lamp (RF-6000, Shimadzu, Japan). The concentration of the carbon dots in the solution system was 0.25 mg / mL. The results are shown in Table 1. Figure 3 As shown in C, it shows that UV irradiation for 5 h has no obvious effect on the fluorescence of OT-FeCDs.

[0089] (4) Effect of storage conditions at room temperature: The OT-FeCDs solution was placed at room temperature for a period of time, and fluorescence was measured in a fluorescence spectrophotometer equipped with a xenon lamp (RF-6000, Shimadzu, Japan). The concentration of the carbon dots in the solution system was 0.25 mg / mL. Figure 3 As shown in C, it shows that placing it at room temperature for 48 hours has no obvious effect on the fluorescence of OT-FeCDs.

[0090] The above results confirm that the carbon quantum dots of the present invention are insensitive to ionic strength, pH changes, and ultraviolet irradiation, and there is no obvious change in fluorescence intensity when stored for a long time at room temperature; this shows that the carbon quantum dots of the present invention have good stability and are convenient for storage, transportation, and actual clinical application.

[0091] Experimental Example 3: Verification of the quantitative relationship between carbon quantum dots OT-FeCDs and DX1002 quenching

[0092] 1. The effect of the concentration of carbon quantum dots OT-FeCDs in the detection system on the quenching relationship between OT-FeCDs and DX1002: Accurately measure and prepare 50 μL of OT-FeCDs solutions of different concentrations and DX1002 reference solutions with concentrations of 20, 60, 100, 300, and 500 μg / ml in a 0.5 mL EP tube, accurately add 100 μL of ultrapure water, mix well to obtain the solution to be tested, and accurately measure 170 μL in a 96-well plate. The fluorescence value of each well was measured by an enzyme reader (Ex / Em=560 / 610 nm), and the fluorescence intensity F after the action of DX1002 corresponding to the OT-FeCDs solution of different concentrations was obtained, and a standard curve of fluorescence quenching degree (F0 / F)-concentration (Q) was prepared (F0 is the fluorescence intensity of the system without the addition of the quencher OT-FeCDs).

[0093] from Figure 4 It can be seen that the carbon dots concentration in the test solution is in the range of 0.25-2.5 mg / mL, and has a quantitative quenching relationship with DX1002. Among them, when the carbon dots concentration in the test solution is 0.25 mg / mL, the quenching relationship with DX1002 is most obvious. Therefore, subsequent tests are carried out with a carbon dots concentration of 0.25 mg / mL in the test solution.

[0094] 2. Effect of the concentration of DX1002 in the detection system on the quenching relationship between OT-FeCDs and DX1002: According to the determination method of Example 2: accurately measure 50 μL of the prepared OT-FeCDs solution (1 mg / mL) and DX1002 reference solution of different concentrations into a 0.5 mL EP tube, accurately add 100 μL of ultrapure water, mix well to obtain the solution to be tested, and accurately measure 170 μL into a 96-well plate. The fluorescence value of each well is measured by an enzyme reader (Ex / Em=560 / 610nm), and the fluorescence intensity F after the action of OT-FeCDs corresponding to the DX1002 solution of different concentrations is obtained, and a standard curve of fluorescence quenching degree (F0 / F)-concentration (Q) is prepared (F0 is the fluorescence intensity of the system without the addition of the quencher OT-FeCDs).

[0095] like Figure 1 As shown, it was confirmed that OT-FeCDs and DX1002 had a good linear relationship in the DX1002 concentration range of 7.5 to 250 μg / mL.

[0096] Also according to the determination method of Example 2, the OT-FeCDs carbon quantum dots were replaced with the carbon quantum dots of Comparative Examples 1 to 4:

[0097] Comparative Example 1: The fluorescence value of each well was measured by an ELISA instrument (Ex / Em=420 / 680nm), and the fluorescence intensity of DX1002 solutions with different concentrations after reacting with SOCDs was obtained;

[0098] Comparative Example 2: The fluorescence value of each well was measured by an ELISA instrument (Ex / Em=420 / 565nm), and the fluorescence intensity of DX1002 solutions with different concentrations after the reaction with OCDs was obtained;

[0099] Comparative Example 3: The fluorescence value of each well was measured by an ELISA instrument (Ex / Em=380 / 565nm), and the fluorescence intensity of DX1002 solutions with different concentrations after the reaction with OTCDs was obtained;

[0100] Comparative Example 4: The fluorescence value of each well was measured by an ELISA instrument (Ex / Em=420 / 572nm), and the fluorescence intensity of DX1002 solutions with different concentrations after the reaction with OFCDs was obtained;

[0101] The relationship between the fluorescence intensities of DX1002 solutions with different concentrations in each comparative example is as follows: Figure 5 As shown. Figure 5 It can be seen that there is no quantitative quenching / enhancement effect between the carbon dots in comparative examples 1 to 4 and DX1002, and there is no quantitative linear relationship between the fluorescence intensity and the concentration of DX1002. The carbon dots in comparative examples cannot be used for quantitative detection of DX1002.

[0102] 3. Effect of temperature on quenching relationship: Refer to the methods in Spectrochimica acta, Part A. Molecular and biomolecular spectroscopy, 2019, 212167-172 and Talanta: The International Journal of Pure and Applied Analytical Chemistry, 2018, 188788-794 to verify the effect of temperature on the quenching relationship of the carbon dots of the present invention on DX1002. Figure 6 It can be seen that the change of temperature between 25 and 45° C. has no effect on the fluorescence quantitative quenching relationship between the carbon quantum segment OT-FeCDs of the present invention and DX1002.

[0103] The above results indicate that the carbon dots OT-FeCDs prepared by the specific raw materials and method of the present invention have an obvious quantitative quenching relationship with DX1002 in a wider concentration range compared with a variety of other carbon dots, and the concentration change and temperature change of the carbon dots OT-FeCDs in the detection system have no obvious effect on the quantitative quenching relationship. Therefore, the carbon dots OT-FeCDs of the present invention are very suitable for use in reagents for quantitative detection of DX1002, and for establishing a quantitative detection method for DX1002.

[0104] Experimental Example 4: Effect of biological sample background on the fluorescence of OT-FeCDs carbon dots of the present invention

[0105] Take 100 μL of plasma and tissue homogenate blank samples respectively into 0.5 mL EP tubes, add 50 μL of 1 mg / ml OT-FeCDs solution and 50 μL of pure water, mix well and add into the fluorescence micro-cuvette, and measure the fluorescence spectrum with a fluorescence spectrophotometer. Figure 7 The plasma and tissue homogenate have little interference on the fluorescence of carbon dots. After mixing, the fluorescence intensity of carbon dots decreases slightly, but the fluorescence peak position is not affected. The maximum excitation and emission are still 560 / 610nm, indicating that the fluorescence of carbon dots has strong anti-interference ability and can be used for quantitative detection of DX1002 in biological plasma and tissue homogenate samples.

[0106] Experimental Example 5: Analysis and verification of the method for quantitative detection of DX1002 in biological samples of the present invention

[0107] 1. Feasibility analysis: According to the linear equation analysis of Examples 1 to 2, it can be seen that the degree of fluorescence quenching of the biological sample system and the concentration of DX1002 have a good linear relationship in aqueous solution, plasma and tissue homogenate, indicating that the biological background has little interference with the fluorescence of the carbon dots. When analyzing plasma samples, no pretreatment is required. As long as the blood samples collected are not hemolyzed and the clarity of the plasma samples is guaranteed as much as possible, the accuracy of the analysis results can be guaranteed; when collecting biological tissue samples, the interference of blood samples can be removed to the greatest extent through tissue perfusion, and pure tissue samples can be obtained to ensure the accuracy of the measurement results. Therefore, it is feasible to establish a fluorescence analysis method for DX1002 in various biological samples using OT-FeCDs as a fluorescent probe.

[0108] 2. Precision and recovery rate

[0109] According to the determination method of Example 2, the recovery rate experiment of DX1002 solution at different concentration levels was carried out. The results are shown in Table 3. When the amount of DX1002 added to each biological sample was 10.0, 20.0, and 30.0 μg, the recovery rate of DX1002 in plasma was 93.3% to 102%, and the intra-day and inter-day precision RSDs were 1.87% and 2.23%, respectively; the average recovery rate of DX1002 in tissue was 96.5% to 102%, and the intra-day and inter-day average RSDs were 2.14% and 1.96%, respectively. This shows that the method has good accuracy and precision for the actual detection of plasma and tissue samples, and is practical.

[0110] Table 3 DX1002 recovery experiment in biological samples

[0111]

[0112] 3. Selectivity

[0113] The effects of the following common ions, sugars, amino acids and other potential coexisting substances in biological samples on the fluorescence intensity of the DX1002-OT-FeCDs system were investigated: K + (100g·L -1 ),Mg 2+ (100g·L -1 ), Na + (100g·L -1 ), Ca 2+ (100g·L -1 ), Fe 3+ (0.2g·L -1 ),Cu 2+ (0.2g·L -1 ), sucrose (100 g·L -1 ), glucose (100g·L -1 ), leucine (10 g·L -1 )、Glycine (100g·L -1 ), histidine (10 g·L -1 ), alanine (10 g·L -1 ). Add 50 μL of 1 mg / mL OT-FeCDs solution, 50 μL of 0.2 mg / mL DX1002 solution and 100 μL of the above coexisting substance solution into a 0.5 mL EP tube to examine the selectivity of the method and record the fluorescence value.

[0114] The results are shown in Table 4. When the relative error is within ±5.0%, the common potential coexisting substances in the biological samples investigated have almost no interference with the fluorescence signal of the system, indicating that this method has a certain specificity and can be used for DX1002 content detection.

[0115] Table 4 Selectivity investigation of coexisting substances

[0116]

[0117] Experimental Example 6: Pharmacokinetic Analysis and Tissue Distribution Study of Actual Samples

[0118] 1. Pharmacokinetic analysis: The OT-FeCDs-DX1002 biological sample analysis method established in Example 2 was applied to actual sample detection. The plasma drug-time curve of mice after intragastric administration of DX1002 was fitted and analyzed using DAS 2.0 software. The drug-time curve was as follows: Figure 8 ; The main pharmacokinetic parameters of the drug in plasma are shown in Table 5.

[0119] Table 5 Pharmacokinetic parameters of DX1002

[0120]

[0121] Compared with the commonly used LC-MS / MS method for single sample analysis, this method only takes 0.2s to analyze a single sample, eliminating the tedious pre-treatment process of mass spectrometry analysis, greatly saving analysis time and reducing costs. It can also measure the fluorescence intensity of 60 samples at the same time, shortening the total analysis time by nearly 1500 times, and realizing high-throughput pharmacokinetic measurements.

[0122] 2. Tissue Distribution Study After mice were intragastrically administered with 400 mg / ml DX1002, the tissue distribution of DX1002 at 5, 25, and 240 min was quantitatively determined according to the method of Example 2. Fig. 9 The figure shows the content of DX1002 in tissues at different time points. It can be seen that DX1002, as a lung cancer treatment drug, can maintain a high concentration level in the lungs for a long time, indicating that DX1002 has a certain tissue distribution targeting.

[0123] It can be seen that the detection method of the present invention provides an effective means for the pharmacodynamic study of DX1002.

[0124] In summary, the present invention provides a carbon quantum dot having excellent optical properties such as fluorescence stability and resistance to biological background quenching, and the characteristic of being quantitatively quenched by DX1002. A method for quantitatively detecting DX1002 is constructed using the carbon quantum dot as a fluorescent probe. The method can skip tedious sample pretreatment and is a rapid, sensitive, economical, and high-throughput DX1002 analysis method, which is suitable for pharmacokinetic monitoring of DX1002, promotes further analysis and research on the anticancer drug candidate DX1002, and also provides new methods and ideas for the high-throughput detection application of carbon quantum dots in biological samples, so as to better meet the rapid detection needs of hospitals and testing centers.

Claims

1. A method for quantitatively detecting the tumor vascular inhibitor DX1002, characterized in that: The steps include: (1) Take carbon quantum dots, dissolve them in pure water to obtain a carbon quantum dot solution, and measure the fluorescence intensity F0 of the carbon quantum dot solution; (2) adding the carbon quantum dot solution of step (1) to the sample to be tested and mixing to obtain a solution to be tested; Determine the fluorescence intensity F of the solution to be tested; (3) Substitute the fluorescence intensities F and F0 measured in steps (1) and (2) into the regression equation F0 / F=f(Q) and calculate the Q value, which is the concentration of DX1002; Wherein, the sample to be tested is plasma, and the regression equation is: F0 / F=0.0024Q+1.0053; Or, the sample to be tested is liver tissue fluid, and the regression equation is: F0 / F= 0.0021Q+0.9981; Or, the sample to be tested is lung tissue fluid, and the regression equation is: F0 / F=0.0021Q+0.9986; Or, the sample to be tested is renal tissue fluid, and the regression equation is: F0 / F=0.0021Q+1.0186; The carbon quantum dots are prepared from the following raw materials: o-phenylenediamine, tryptophan and iron salt.

2. The method according to claim 1, characterized in that The iron salt is at least one of ferric chloride or its hydrate, ferric sulfate or its hydrate.

3. The method according to claim 2, characterized in that The iron salt is ferric chloride hexahydrate.

4. The method according to any one of claims 1 to 3, characterized in that: The molar ratio of o-phenylenediamine, tryptophan and iron salt is: 4:1:(1.2-12).

5. The method according to claim 4, characterized in that The molar ratio of o-phenylenediamine, tryptophan and iron salt is 4:1:

7.

6. The method according to any one of claims 1 to 3, characterized in that: The measurement conditions of steps (1) and (2) are to measure the fluorescence intensity at an emission wavelength of 610 nm at an excitation wavelength of 560 nm.

7. The method according to any one of claims 1 to 3, characterized in that: The concentration of DX1002 in the test sample is 7.5-250 μg / mL.

8. The method according to any one of claims 1 to 3, characterized in that: The concentration of carbon quantum dots in the test solution of step (2) is 0.125~2.5 mg / mL.

9. The method according to claim 8, characterized in that The concentration of carbon quantum dots in the test solution in step (2) is 0.25 mg / mL.

Citation Information

Patent Citations

  • Styrene acid derivative and use in preparation of various blood-vessels target agent medicine

    CN101074189B

  • Preparation method and product of full-color carbon dots for multi-color fluorescent printing

    CN108587615A

  • Synthesis method of green light carbon quantum dots

    CN109913213A